Direct and Indirect Effects of Self-Esteem on Financial Satisfaction - Antony, Jibin; Job, Binu Mathew; Thomas, Antony (International Journal of Economics and Financial Issues, 2024)
In this study, we explore the role of self-esteem on financial satisfaction and propose that self-esteem relates to financial satisfaction both directly as well as indirectly through financial behavior. Data for this study was obtained from a multistage random sample of household financial officers in Kerala, India (n = 500). Results showed that self-esteem significantly relates to household financial officers’ financial satisfaction after controlling for financial knowledge and sociodemographic factors. The relationship between self-esteem and financial satisfaction could be both direct and indirect through financial behavior. The findings suggest that financial educators and financial therapists should work together to enhance not only objective financial knowledge but also psychological traits such as self-esteem for engaging in desirable financial behavior, which in turn relates to financial satisfaction.